The contamination of intravenous fluids by writing on the infusion bag: Fact or fiction? - Langston, James Daniel; Monaghan, William Patrick; Bush, Mellissa (International Journal of Advanced Nursing Studies, 2014)
Introduction -Laboratory experiments were conducted to ascertain whether Sharpie® brand black permanent marker ink will permeate through intravenous infusion bags. The practice of writing directly on infusion bags is a frequent yet controversial practice. There are no known written standards that exist which pertain to this practice. Methods – Five types of intravenous bags containing different solutions marked with black ink from a fine point felt tipped Sharpie® marker. Sample extraction occurred after infusion bags had been warmed to 40 C or remained ambient. Spectrophotometric scans and measurements were conducted at 300 to 600 NM on each solution contained in the experimental bags. Writing with Sharpie® pens on filter paper and surgical tape was also conducted. Results – A total of 17 experiments were conducted with intravenous bags of five different types of manufacture. There appeared to be no visible or ultraviolet spectrophotometric evidence of leaching of the ink from Sharpie® pens. Four different lot numbers of Sharpie® pens were used. Surgical tape that was written on using Sharpie® markers readily exhibited visible evidence of permeability. Discussion - The experiments conducted would appear to indicate that the infusion containers tested maintained an intact barrier to the application of Sharpie® brand permanent marker ink. Writing on surgical tape does not stop the permeability of Sharpie® pens. This study could serve as a suitable pilot study for others to conduct a much more comprehensive study using a greater number of intravenous containers, solutions and ink markers. Keywords: Fluid therapy, infusion, ink, intravenous, writing.